Polycystic ovary syndrome induced by exposure to testosterone propionate and effects of sympathectomy on the persistence of the syndrome - Leticia Morales-Ledesma; Juan Antonio Díaz Ramos; Angélica Trujillo Hernández (BMC, 2017)
Abstract Background Polycystic ovary syndrome is a complex disorder affecting 6 to 10% of women of reproductive age. In recent years, the cause of the syndrome has been associated with increased androgen serum levels, as well as sympathetic nervous system hyperactivity. The present study analyzed the effects at birth of a single testosterone propionate dose in rats, as well as the role of the superior ovarian nerve in polycystic ovary syndrome persistence. Methods Newborn female rats of the CIIZV strain were injected with a single dose of 100 μg testosterone propionate, or corn oil as a vehicle. At 24 days of age, rats were subjected to superior ovarian nerve unilateral or bilateral section. A group of animals was sacrificed on their first vaginal estrus, and a second group was sacrificed at 90 days of age, when they presented an estrus preceded by a proestrus. Results Testosterone propionate administration at birth blocked ovulation both in adult animals and in animals sacrificed on the first vaginal estrus. Histological analysis of testosterone propionate-treated adult rat ovaries revealed the development of follicular cysts. Ovulation could not be restored by unilateral or bilateral section, and ovaries presented follicular cyst and absence of corpora lutea. Conclusions Our results suggest that testosterone propionate treatment at birth results in the development of polycystic ovary syndrome, and that this outcome is not due to superior ovarian nerve noradrenergic innervation hyperactivity.